2020
DOI: 10.1159/000508226
|View full text |Cite
|
Sign up to set email alerts
|

Do Follicles of Obese Patients Yield Competent Oocytes/Embryos?

Abstract: Aim: This study evaluated the competency of oocytes/embryos derived from follicles >15 mm in diameter from obese patients, compared with nonobese patients. Patients and Methods: A cohort study was conducted in a single tertiary medical center between July 2018 and May 2019. Before ultrasound-guided follicular aspiration, follicles were measured and those with maximal dimensional size >15 mm were tracked. Microscopic examination of the follicular aspirates was performed by an embryologist. Each follicle aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This reduction in BMI in both the women that underwent clomiphene citrate treatment and control group with successful ovulation explains the finding from a previous study that obese women with PCOS are more likely than thin women with PCOS to suffer from anovulation [18]. Popova et al [19], found that lean women with PCOS treated with metformin had menstrual function (55%) and ovulation (45%) restored more often than obese women with PCOS (only one patient (7%) responded to the treatment), P = 0.018. There was no change in BMI and waist circumference in both groups.…”
Section: Table 1 Mean Values Of Body Mass Index Of Women With Polycys...mentioning
confidence: 69%
See 1 more Smart Citation
“…This reduction in BMI in both the women that underwent clomiphene citrate treatment and control group with successful ovulation explains the finding from a previous study that obese women with PCOS are more likely than thin women with PCOS to suffer from anovulation [18]. Popova et al [19], found that lean women with PCOS treated with metformin had menstrual function (55%) and ovulation (45%) restored more often than obese women with PCOS (only one patient (7%) responded to the treatment), P = 0.018. There was no change in BMI and waist circumference in both groups.…”
Section: Table 1 Mean Values Of Body Mass Index Of Women With Polycys...mentioning
confidence: 69%
“…They concluded that treatment with metformin 1700 mg daily was more effective in lean than in obese women with PCOS. Its efficacy was independent of the initial surrogate markers of resistance to insulin [19].…”
Section: Table 1 Mean Values Of Body Mass Index Of Women With Polycys...mentioning
confidence: 97%